2017
DOI: 10.1038/nm.4386
|View full text |Cite|
|
Sign up to set email alerts
|

Sex-specific transcriptional signatures in human depression

Abstract: Summary Major depressive disorder (MDD) is a leading cause of disease burden worldwide. While the incidence, symptoms and treatment of MDD all point toward major sex differences, the molecular mechanisms underlying this sexual dimorphism remain largely unknown. Here, combining differential expression and weighted gene coexpression network analyses, we provide a comprehensive characterization of male and female transcriptional profiles associated with MDD across 6 brain regions. We overlap our human profiles wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

51
593
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 608 publications
(684 citation statements)
references
References 106 publications
51
593
9
Order By: Relevance
“…Recent studies which examined the molecular pathology of MDD report distinct molecular changes in men and women across several mesocorticolimbic brain regions [23, 46]. However, it is unclear which sex-related factors might drive this distinct MDD-associated pathology in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies which examined the molecular pathology of MDD report distinct molecular changes in men and women across several mesocorticolimbic brain regions [23, 46]. However, it is unclear which sex-related factors might drive this distinct MDD-associated pathology in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that CVS produces similar levels of depressive behaviors in both males and females demonstrates a limitation of this model. Nevertheless, transcript analysis in the Labonté et al 6 study shows very low overlap of DEGs (20–25%) between female and male mice exposed to CVS in the two brain regions examined (the vmPFC and nucleus accumbens). Importantly, the results also show substantial overlap of DEGs, modules, and hub genes in female mice exposed to CVS as compared to women with depression, as well as in male mice exposed to CVS relative to men with depression (for example, in the vmPFC, there are 251 up- or downregulated transcripts conserved in females, and 152 in males), demonstrating that the CVS-exposed mouse is a valid model system.…”
mentioning
confidence: 84%
“…Despite these efforts, the heterogeneity of depression and the problems inherent in identifying illness-related gene variants have made it difficult to identify the molecular and neurobiological bases of depression, particularly, the greater incidence of the condition in women. In this issue, Labonté et al 6 use a bioinformatics approach 7,8 to demonstrate that depression is characterized by different disease-associated gene modules in the postmortem brains of women relative to those in men, and that these modules are conserved in mice. The findings define for the first time the notable sexually dimorphic gene-expression networks in key brain regions that are implicated in depression, and so will help to elucidate the pathophysiology of and potential avenues for treating depression, particularly in women.…”
mentioning
confidence: 99%
“…A recent study has started to explore differences in gene expression that could further explain the observed sexual dimorphism in MDD [77••]. The study reports on sex-specific disease-associated modules identified in postmortem brains of depressed male and female subjects.…”
Section: Sexual Dimorphism In Mddmentioning
confidence: 99%